Students' readiness in online learning (A Case study in higher Education) - Bimantara Ardhi Kusuma; Wulan Suci Ramadani; Riva Guntur Laksono; Meiga Ratih Tirtanawati; Ima Isnaini Taufiqur Rohmah; Ikariya Sugesti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2022)
The Covid-19 pandemic has a very complex impact on modern human life. Referring to this phenomenon, we found a problem, namely the students’ readiness. We examine this problem from 2 dimensions, (1) are the infrastructure owned by students adequate? and (2) whether students can focus and concentrate in online learning. The current research under qualitative case study, where interview and observation were used in collecting the data. The results of the study show that (1) it's pretty good, almost all students have adequate infrastructure such a phone-cell (65%), and also personal computer (11%) and laptop (24%); (2) Overall students have been able to receive lessons in online learning. However, there are obstacles in the interaction of students with teachers, especially for students with high anxiety. Further study that focused on the reason of students’ anxiety is need to conducted to get a whole understanding of students’ readiness.